A PERSPECTIVE OF DIGITAL ACCOUNTING AND DIGITAL LITERACY ON FINANCIAL STATEMENT PREPARATION IN THE CONTEXT OF LAW NO. 18/2019: PERSPECTIVE OF DIGITAL ACCOUNTING AND DIGITAL LITERACY ON FINANCIAL STATEMENT PREPARATION IN THE CONTEXT OF LAW NO. 18/2019 - hary pribadi, tegar; Sri Wahyuni, Endah; Alfiyan (Faculty of Law, Universitas Pekalongan, 2025)
Several Islamic boarding schools (pesantren) have established and rapidly developed MSMEs. This study was conducted at the Al-Bismi Islamic Boarding School Association. The objective of this research is to analyze the influence of digital accounting and digital literacy on the preparation of financial statements in MSME Al-Bismi. This study employs an explanatory research approach. It is a quantitative study that tests hypotheses using Partial Least Squares (PLS). The research subjects include the Islamic boarding school administrators and students managing the pesantren-owned MSMEs. The variables examined in this study are digital accounting, digital literacy, and financial statement preparation. The findings indicate that partially digital accounting influences financial statement preparation, and digital literacy also has an impact on financial statement preparation. It is known that not all caregivers of Islamic boarding schools fully understand the regulations governing these laws. However, the majority of students majoring in accounting comprehend and support the regulations by enhancing their accounting competencies. Additionally, students from non-accounting majors also support these regulations and are committed to developing the business ventures of the Islamic boarding schools.